Distinct Malignant Behaviors of Mouse Myogenic Tumors Induced by Different Oncogenetic Lesions - Hettmer, Simone; Bronson, Roderick T.; Wagers, Amy J. (Frontiers in Oncology, 2015)
Rhabdomyosarcomas (RMS) are heterogeneous cancers with myogenic differentiation features. The cytogenetic and mutational aberrations in RMS are diverse. This study examined differences in the malignant behavior of two genetically distinct and disease-relevant mouse myogenic tumor models. Kras; p1619null myogenic tumors, initiated by expression of oncogenic Kras in p16p19null mouse satellite cells, were metastatic to the lungs of the majority of tumor-bearing animals and repopulated tumors in 7 of 9 secondary recipients. In contrast, SmoM2 tumors, initiated by ubiquitous expression of a mutant Smoothened allele, did not metastasize and repopulated tumors in 2 of 18 recipients only. In summary, genetically distinct myogenic tumors in mice exhibit marked differences in malignant behavior.